Normative Data for Single- and Dual-Task Tandem Gait Performance in Collegiate Athletes. - Shumski, Eric J.; Lempke, Landon B.; Howell, David; Buckley, Thomas; Oldham, Jessie; Meehan, William; Lynall, Robert C. (Sports Medicine, 2026)
Background: Normative dual-task (concurrent cognitive and motor task) tandem gait has not been developed. Currently, only individual baseline data are used for tandem gait assessment post concussion. Objective: The object was to (1) determine factors associated with single-task and dual-task tandem gait time among collegiate athletes across multiple institutions, and (2) provide robust normative data for single-task and dual-task tandem gait time based on clinically relevant factors. Methods: Data were analyzed from 2,137 unique collegiate athletes (19.0 ± 1.1 years, 48.9% female, 23.7% with concussion history) from 2015 to 2022 during pre-injury baseline concussion testing from three universities. Tandem gait was performed under single- and dual-task conditions (serial subtraction by sixes/sevens, spelling five-letter words backward, reciting the months backward). The criteria for being a clinically relevant independent variable was (a) p value < 0.05, and (b) effect estimate of ≥ 1 s. Normative data based on established percentile thresholds were derived and stratified by clinically relevant factors. Results: None of the single-task tandem gait times were clinically relevant, while sex and contact level were for dual task. Mean (95% confidence interval) for overall single- and dual-task tandem gait times were 12.07 s (11.95, 12.19) and 16.51 s (16.29, 16.73), respectively. Conclusion: Our results provide robust normative data for single- and dual-task tandem gait stratified by relevant patient factors that can be immediately used by clinicians and future researchers. Future research should compare the use of individual baseline versus normative data for acute concussion tracking.